Adsorption of Tetracycline Hydrochloride from Solutions Using Mesoporous Silica, MCM-48 - Taba, Paulina; Mutmainnah, Mutmainnah; Hala, Yusafir (Indonesian Journal of Chemical Research, 2021)
Mesoporous silica with cubic structure (MCM-48) was synthesized using Ludox HS40 as silica source and cetyltrimethylammonium bromide (CTAB) as a template. MCM-48 was used to adsorb the antibiotic of tetracycline hydrochloride. An X-ray diffractometer observed the x-ray diffraction pattern of MCM-48 and functional groups observed by a Fourier Transformed Infrared (FTIR) spectrometer. Parameters used to study adsorption were contact time and concentration. The pseudo-second-order was the kinetic order that fitted well with the adsorption of tetracycline HCl. The adsorption of tetracycline HCl on MCM-48 followed the Freundlich isotherm with the adsorption capacity of 0.98 mg/g.